Analisis Pengaruh Jejaring Sosial Terhadap Interaksi Sosial di Era Digital - Dea Cindi Amelia Ginting; Sri gusti Rezeki; Aldio Azani Siregar; Nurbaiti Nurbaiti (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
The Digital Era has transformed the way humans interact and communicate through the development of information technology and social networks. Social media platforms such as Facebook, Instagram, and Twitter have reshaped the landscape of social interactions, enabling individuals to connect with people worldwide quickly and efficiently. This article conducts an in-depth analysis of the significant influence of social networks on social interactions in the digital era. Social networks facilitate the exchange of information, collaboration, and getting to know each other in various forms, ranging from text to visual and audiovisual content. In this context, there are two key elements in social interactions: social contact and communication. The Uses and Gratifications theory highlight the active role of social media users in choosing and utilizing these platforms to fulfill their needs for entertainment, information, personal identity, and social integration. Despite the convenience they offer, the use of social networks also presents significant challenges, such as privacy issues and social media addiction. It is crucial for individuals to develop a healthy self-awareness regarding their social media usage. Additionally, technology companies and policymakers must prioritize protecting users' privacy and creating an online environment that is healthy, safe, and inclusive for everyone. This analysis not only discusses negative impacts such as privacy and data security but also demonstrates the potential of social networks as powerful tools for building bridges between cultures, ideas, and people worldwide. Therefore, collaboration between society, governments, and corporations is essential in creating a positive and healthy online environment for all users.